Position of DSN-MUI Fatwa No.79 of 2011 Concerning Qará¸ with Customer Funds in the Perspective of MaqÄá¹£id SharÄ«â€˜ah Jasser Auda: Kedudukan Fatwa DSN-MUI. No: 79/DSN-MUI/III/2011 Tentang Qardh Dengan Menggunakan Dana Nasabah Perspektif Maqashid Syariâ€˜ah Jasser Auda - Muhammad Lathoif Ghozali; Anita Musfiroh (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2022)
Abstract: This study will explain the DSN-MUI Fatwa No.79 of 2011 regarding the perspective of MaqÄá¹£id Syari'ah according to Jasser Auda's approach theory. The method used in this study is qualitative with literature study by finding and collecting factual facts or information using the themes and topics that will be or are being researched. This study tries to explain that the system approach theory echoed by JasserAuda is not only rigid but also elastic. So it can be implemented in legal provisions by means of a surgical process through the application of the six-element method which is the criterion, namely cognitive elements, openness, comprehensiveness, interconnected or interrelated hierarchies, meaning, and multidimensionality. As a result, the position of MaqÄá¹£id SharÄ«â€˜ah can be found, and of course, the provisions of the rules can be applied to people's lives with a wide range. Regarding the DSN-MUI Fatwa No. 79 of 2011 concerning Qará¸, it is permissible to use customer funds because it fulfils the elements of the system theory applied by Jasser Auda. Indirectly, the theory of Jasser Auda's system approach is a tool or scale in dissecting the position of MaqÄá¹£id SharÄ«â€˜ah against legal provisions that have been established or will be enforced. Keywords: Systems Theory, Jasser Auda, Qará¸, DSN-MUI Fatwa. Â Abstrak: Penelitian ini menjelaskan Fatwa DSN-MUI No.79 Tahun 2011 tentang Perspektif MaqÄá¹£id SharÄ«â€˜ah menurut teori Jasser Auda. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan model studi literatur yang mencari dan mengumpulkan fakta atau informasi faktual menggunakan tema dan topik yang akan atau sedang diteliti. Penelitian ini menjelaskan bahwa teori pendekatan sistem yang digaungkan oleh Jasser Auda bukan hanya teori kaku namun teori yang elastis juga. Sehingga dapat diimplementasikan dalam ketentuan hukum melalui proses pembedahan, melalui penerapan metode enam unsur yang menjadi kriterianya, yaitu unsur kognitif, keterbukaan, kekomprehensifan, hirarki yang saling berhubungan atau saling berkaitan, makna, dan multidimensionalitas. Alhasil, posisi MaqÄá¹£id SharÄ«â€˜ah dapat ditemukan dan tentunya ketentuan aturannya dapat diterapkan dalam kehidupan masyarakat dengan jangkauan yang luas. Mengenai Fatwa DSN-MUI No. 79 Tahun 2011 tentang Qará¸, boleh menggunakan dana nasabah, karena memenuhi unsur teori sistem yang diterapkan oleh Auda. Secara tidak langsung, teori pendekatan sistem Auda merupakan alat atau skala dalam membedah kedudukan MaqÄá¹£id SharÄ«â€˜ah terhadap ketentuan hukum yang telah ditetapkan atau akan diberlakukan. Kata Kunci: Teori Sistem, Jasser Auda, Qardh, DSN-MUI Fatwa